2017
DOI: 10.17116/jnevro20171175122-25
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the efficacy of reflexology in the complex treatment of chronic migraine

Abstract: Reflexotherapy is a method of choice in the complex treatment of patients with chronic migraine. Taking into account complex diagnosis, the individually oriented approach in prescribing of different reflexology techniques for successful treatment and subsequent rehabilitation of patients with chronic migraine is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
1
13
0
1
Order By: Relevance
“…Cruz and Munoz [9] evaluated the effectiveness of Su Jok therapy in patients with tension-related headache (n = 50) and reported that 80% of the patients had a decrease in the pain intensity and frequency after Su Jok therapy. In another study, the frequency of headache, number of analgesics used, and scores on the Headache Impact Test-6 (HIT-6) questionnaire after Su Jok therapy were found to be significantly lower than those of the control group [10]. Su Jok therapy is defined as the modern interpretation of acupressure/acupuncture therapy on the reflection points on the hands and feet of the patients that can be used in both acute and chronic diseases for symptom improvement and health promotion [12,13].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Cruz and Munoz [9] evaluated the effectiveness of Su Jok therapy in patients with tension-related headache (n = 50) and reported that 80% of the patients had a decrease in the pain intensity and frequency after Su Jok therapy. In another study, the frequency of headache, number of analgesics used, and scores on the Headache Impact Test-6 (HIT-6) questionnaire after Su Jok therapy were found to be significantly lower than those of the control group [10]. Su Jok therapy is defined as the modern interpretation of acupressure/acupuncture therapy on the reflection points on the hands and feet of the patients that can be used in both acute and chronic diseases for symptom improvement and health promotion [12,13].…”
Section: Introductionmentioning
confidence: 93%
“…Hence, buckwheat seeds were used in our study. The intervention procedure was based on the study by Safonov [10]. Accordingly, Su Jok seed therapy was administered twice a week for 4 weeks.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of reflexology vs. acupuncture vs. electroacupuncture vs. control in chronic migraine (n=84), where all patients also received 100mg topiramate daily, showed all groups had improved headache frequency, with reflexology being "most effective in treatment of autonomic disorders;" only the abstract was available in English. (64) An RCT evaluated the effects of reflexology massage vs. sham placebo vs. control (with no treatment) for abortive treatment of a nitroglycerin-induced migraine. Only the reflexology massage treatment resulted in less intense migraine pain.…”
Section: Reflexologymentioning
confidence: 99%
“…7 Most publications concerning the effects of Su Jok therapy focus on physical dimensions such as fatigue and weakness, heel pain, asthma, migraine, rehabilitation of stroke patients, and pain in the elbows, while Su Jok has also been proven to reduce the scale of pain. [8][9][10][11][12][13][14] Although Su Jok is able to help with psychological problems, there is no literature found in English that has been published regarding how effective can be Su Jok in reducing psychological problems, such as fear. Because Su Jok can be considered as an easy method of therapy and also provides a quick result, it is important to explore the benefits of Su Jok for psychological problems, specifically for reducing the feelings of fear.…”
Section: Introductionmentioning
confidence: 99%